Effect of Andrographis paniculata Leaf Crude Extract Against Edwardsiella tarda Bacteria and Histopathological Profile of the Liver of Osphronemus gouramy Juvenil - Giri Pratama; Arief Prajitno; Titik Dwi Sulistiyati (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Paniculata leaf crude extract has antibacterial compounds Paniculata leaf crude extract can inhibit the growth of E. tarda bacteria Gouramy liver infected by tarda bacteria undergoes degeneration, congestion, and necrosis Treatment using paniculata leaf extract can improve Gouramy liver damage   Abstract Edwardsiellosis caused by bacterium E. tarda is a serious challenge faced by Gourami farmers. This study aimed to determine the antibacterial activity of A. paniculata leaf crude extract on the growth of E. tarda bacteria and its effect on the histopathology of gourami liver which was carried out in two stages. In the first stage, the active compound was identified in the leaves of A. paniculata followed by the Minimum Inhibitory Concentration (MIC) test at five different doses and two controls. In-silico test was conducted to determine the antibacterial activity of crude extract of A. paniculata leaf. In the second stage, the Lethal Dosage (LD50) and Toxicity (LC50) tests were carried out. Histopathological test of gouramy liver was carried out by taking the liver of fish that had been exposed to E. tarda bacteria. The active compounds contained in the crude extract of A. paniculata leaf are flavonoids, alkaloids, tannins, triterpenoids, and saponins. The Lethal Dosage (LD50) was 106 CFU/ml, and a toxicity test showed a dose of 250 mg/L caused the most death compared to other treatments. Histopathological test of gouramy liver showed that crude extract of A. paniculata leaf could improve liver function optimally at a dose of 300 (mg/L). The results of this study indicate that crude extract of A. paniculata leaf can affect the histology profile of gouramy liver and can cause toxicity if used inappropriately.